Blunt Trauma Abdomen-Fatal and Non-fatal Liver Injury - Kabir, Sheikh Firoj; Haque, Md Sirajul (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Blunt abdominal trauma is a common feature in modern day-to-day activities including RTA, falling from the height. Liver is the second most frequently injured organ and most common cause of death after abdominal trauma. Management modalities include operative and non-operative measures depending on the state of the patient, pattern of injury, and availability of surgical experts. Here we present 3 cases of blunt abdominal trauma which includes fatal and non-fatal liver injury. One of the patients managed non-operatively and two of them managed with operative techniques. Out of two patients, one died in the second post-operative day. Another patient survived and maintained healthy life after successful management. The non-operative techniques include assessment of patients, vital signs, and radiographic evaluation, volume replacement, blood transfusion, antibiotics, and analgesics. Haemodynamically stable patients are kept in this category. Operative techniques include perihepatic packing, omental packing, hepatorraphy absorbable mesh, and gel foam application. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i2.43 Chatt Maa Shi Hosp Med Coll J 2013; 12(2): 59-62